1999
DOI: 10.1096/fasebj.13.14.2083
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor as a local mediator of the neurotrophic action of vitamin B 12 (cobalamin) in the rat central nervous system

Abstract: We have recently demonstrated that the myelinolytic lesions in the spinal cord (SC) of rats made deficient in vitamin B(12) (cobalamin) (Cbl) through total gastrectomy (TG) are tumor necrosis factor-alpha (TNF-alpha)-mediated. We investigate whether or not permanent Cbl deficiency, induced in the rat either through TG or by chronic feeding of a Cbl-deficient diet, might modify the levels of three physiological neurotrophic factors-epidermal growth factor (EGF), vasoactive intestinal peptide (VIP), and somatost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 51 publications
(72 reference statements)
3
40
1
Order By: Relevance
“…35,36 We found similar results in AD patients with lower plasma Vit B 12 and EGF levels and higher plasma TNF- levels than the controls. Vit B 12 was reported to down regulate the expression of TNF- and EGF genes in addition to its hormone-like and coenzyme functions in the central nervous system.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…35,36 We found similar results in AD patients with lower plasma Vit B 12 and EGF levels and higher plasma TNF- levels than the controls. Vit B 12 was reported to down regulate the expression of TNF- and EGF genes in addition to its hormone-like and coenzyme functions in the central nervous system.…”
Section: Discussionsupporting
confidence: 76%
“…Vit B 12 was reported to down regulate the expression of TNF- and EGF genes in addition to its hormone-like and coenzyme functions in the central nervous system. 36 Studies suggested that Vit B 12 was an essential factor for the signaling pathway of the central nervous system of rats and that VitB 12 deficiency with the absence of EGF which is a neurotropic factor, was associated with central neuropathy. 37 Vit B 12 replacement normalized the EGF levels in the CSF and EGF m-RNA expression in various areas of the central nervous system in rats that underwent total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We recently have identified a potential mechanism by which chronic Cbl deficiency causes SCD in rats: the locally increased production of a myelinolytic agent (tumor necrosis factor [TNF]-␣) 5 combined with the locally decreased production of the neurotrophic agent epidermal growth factor (EGF). 6 Even more importantly, we also have found that the same imbalance in TNF-␣ and EGF levels occurs in the serum of humans with clinically confirmed severe Cbl deficiency (but not in patients with pure irondeficiency anemia) and can be corrected when the severe Cbl deficiency is corrected by Cbl therapy. 7 These results prompted us to verify whether the imbalance in TNF-␣ and EGF levels in favor of the former also occurs in the cerebrospinal fluid (CSF) of patients with SCD.…”
mentioning
confidence: 64%
“…8 In contrast, there are relatively low levels of EGF mRNA expression in the brain. 9 EGF receptors (EGFR) are widely present in both the developing and mature central nervous system (CNS). [10][11][12] EGF and structurally related peptides have been studied extensively with respect to the growth and survival of midbrain dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%